Business Model Innovation: The Role of Organizational Design - Klement Ahrensbach Rasmussen (Copenhagen Business School (CBS), 2017)
The topics of business model innovation (BMI) and organizational design have potentially important links. And yet, there has been little cross-fertilization of ideas between the two fields. The purpose of this thesis is to fill that gap by proposing and developing an organizational view of BMI that focuses on the missing links between business model innovation and organizational design theory. Guided by the research question—what is the role of organizational design in the process of business model innovation?—the thesis not only investigates how BMI activity unfolds, but also looks at the different roles of the firm's organizational design and where the activity takes place. Moreover, this research provides ample detail on how organizational complementarities emerge or vanish as a result of the fit or misfit between business model elements and design choices. To drive home these important points, I rely on insights from a multiple-case study of three pharmaceutical companies: Novo Nordisk, UCB and LEO Pharma.
hdl:10398/9505
Keywords: 650